Pulsatile Physiological Control of Blood Pump-Cardiovascular System Based on Feedforward Compensation - Yanjun Bao; Teng Jing; Weimin Ru; Ling Zhou (Micromachines)
Rotary Blood Pump (RBP) is a commonly used ventricular assist device. However, the constant speed operation of the blood pump leads to a reduction of blood flow pulsatility, which triggers a series of adverse reactions. In this paper, a pulsatile physiological control with feed-forward compensation (FFC) is designed to regulate the rotational speed in real time to accurately output pulsatile blood flow to address this problem. The coupled model of the Rotary Blood Pump and cardiovascular system (CVS) is established in the SIMULINK software as the research object. The designed pulsatile physiological control algorithm contains the feed-forward compensation-based pulsatile control and anti-reflux algorithm, switching the applicable algorithm based on the pump flow. When the flow rate is higher than the threshold, feed-forward compensation is introduced and combined with PI feedback control to improve the performance of pulsation tracking; when the flow rate is lower than the threshold, it is switched to the anti-reflux algorithm to gradually increase the pump speed. Simulation shows that the designed feed-forward compensation link reduces the tracking error of the pulsatile physiological control by 80%. In the case of a 50% sudden change of physiological parameters, it can track quickly and stably and avoid reflux. The pulsatile performance and ventricular unloading performance are better compared with no feed-forward compensation pulsation control as well as constant-speed control. An increase of 30 mmHg in aortic beat-to-beat differential pressure was achieved in the extracorporeal circulation experiments, which is important for the realization of pulsatile flow control of the Rotary Blood Pump.